Determinants of Entrepreneurial Intention among Higher Education Students: The Role of Entrepreneurship Education, Social Environment, and Self-Efficacy - Margaretha S. Kabanga; Janri D. Manafe; Tuti Setyorini (CV. Vocezmi Learnov, 2026)
This study aims to examine the determinants of entrepreneurial intention among higher education students by integrating entrepreneurship education, social environment, and self-efficacy within the Theory of Planned Behavior framework. A quantitative explanatory approach was employed using survey data collected from 231 final-year students at Kupang State Polytechnic. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) to assess both measurement and structural models. This study extends the application of the Theory of Planned Behavior by empirically demonstrating the dominance of perceived behavioral control, represented by self-efficacy, over attitude and subjective norms in shaping entrepreneurial intention. It provides contextual evidence from an underexplored higher education setting, offering a more nuanced understanding of TPB components. The findings suggest that higher education institutions should prioritize experiential entrepreneurship learning to strengthen students’ self-efficacy, alongside fostering supportive social environments to enhance entrepreneurial intention. This study is limited by its cross-sectional design, single-institution sample, and reliance on self-reported data. Future research should adopt longitudinal approaches and incorporate broader contextual variables to improve generalizability.